HOMES WITH SOUL : DESIGNING WITH HEART - Robinzone, Orly; Arik, Limor Zomer; Adams, Shy (Mulgrave, Victoria, Australia : Images Publishing Group Pty Ltd, 2018)
Sumptuously illustrated with photographs and room schemes that are bound to inspire, The Emotional Home is the definitive interior design guide from renowned designer, Orly Robinzon. This stunning book showcases inspiring images of the room schemes of some of her latest projects. Offering invaluable advice on creating beautiful aesthetic spaces for making a home, home, Robinzon shares her inspirational tips and advice to help you with your next home-decorating project, however big or small in scale, to ensure it is functional, beautifully designed, and provides an interior that blends seamlessly with any landscape or outdoor environment, and which suits the way you live. Robinzon provides expert guidance on her use of colour, texture, lighting, furniture, art and other decorative elements to create a comfortable and elegant home that imbues an emotional response, and resonates with those looking to create a stylish and cosy sanctuary at home.
Keywords: Robinzone, Orly -- Themes, motives; Interior decoration -- Israel; Architectural design -- Israel; House furnishings -- Israel; Photobooks